2020
DOI: 10.1177/0361198120935443
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Traffic Efficiency and Safety by Varying Truck Platoon Characteristics in a Critical Traffic Situation

Abstract: Truck platooning is the application of cooperative adaptive cruise control where multiple trucks are electronically linked using vehicle-to-vehicle communication. Although truck platoons might bring fuel savings and emission reductions, their interactions with surrounding traffic and resulting impact on traffic operations and safety are not fully understood. The objective of this paper is to evaluate traffic efficiency and safety in a critical traffic situation when truck platoons are introduced in the system.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Nevertheless, decreasing the number of vehicles in the platoon slightly enhanced the traffic safety and decreased the number of traffic conflicts. This result was previously reported by both [27,28], who explained that a higher number of vehicles in a platoon reflects more braking actions which may result in a higher number of conflicts.…”
Section: The Key Parameterssupporting
confidence: 87%
See 2 more Smart Citations
“…Nevertheless, decreasing the number of vehicles in the platoon slightly enhanced the traffic safety and decreased the number of traffic conflicts. This result was previously reported by both [27,28], who explained that a higher number of vehicles in a platoon reflects more braking actions which may result in a higher number of conflicts.…”
Section: The Key Parameterssupporting
confidence: 87%
“…Finally, because a greater number of vehicles in a platoon reflects more braking actions [27,28], the maximum number of vehicles in a platoon (platoon size) is important for traffic safety. The default maximum platoon size for Aimsun is ten vehicles.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Aggressiveness in the car-following behavior is assessed through a time-to-collision-based (TTC) indicator. The aggressiveness is assumed to be present if the TTC value is less than 4 s, which is also used in previous research [24,25]. 8.…”
Section: A Trajectory Datamentioning
confidence: 99%
“…Fiber et al found the truck platooning using CACC, moving on the mainline at merging section, has detrimental effects on traffic safety. The regulations for rolling out of CAVs and liability related to road safety have not been addressed properly worldwide [ 39 ].…”
Section: Effects Of Cavs On Transportation Performancementioning
confidence: 99%